Transiç\~ao energética e potencial de cooperaç\~ao nos Brics em energias renováveis e gás natural - Luciano Losekann; Amanda Tavares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The BRICS are characterized by the diversity of energy systems, socioeconomic structures, and institutional frameworks. Therefore, the energy transition process assumes particular trends in each country. Despite the high share of fossil fuels in the energy mix, the BRICS are engaged in promoting clean energy sources. Expanding cooperation in the area of energy is seen as a way to seize opportunities for complementarity. This study analyzes the initiatives and opportunities for cooperation in the BRICS energy transition process at bilateral and multilateral levels, with a focus on the diffusion of renewable sources and natural gas. The first part of the study describes the evolution of the BRICS energy mix and policies for the diffusion of renewable energies and natural gas as a way to mitigate CO2 emissions. The second part of the report addresses energy cooperation among the BRICS, presenting the initiatives already developed, prospects and opportunities.
Keywords: F15; O13; P18; Q42; Q48; 330; BRICS; cooperation; renewable energy; natural gas; energy efficiency; CO2 emissions